Constitutional Transparency in the selection of ministers and prepare ministerial curriculum( Comparative Study ) - A. Abbood , Haider; M. Abdullatif , Prof.Dr.Samir (Basra studies journal, 2022)
The right to know goes hand in hand with the extension of democratic culture and the establishment of the rule of law and the ability to govern with integrity and clarity. And, this is achieved by the commitment of departments to spread information and the availability of effective mechanisms through which the public can obtain information and access to information to achieve transparency in the work of the executive. It also strengthen the unity of the state to avoid the collapse of the country. On the other hand, the expansion of transparency is not understood without restrictions and limits. Moreover, the greater the degree of transparency, the greater the degree of sense of equality and justice, and results in efficient decisions related to the institution. State should move away from the secrecy in the realization which is considered as the cover for the senior positions holders to legitimize corruption in state facilities, especially in the framework of the selection of ministers, and ministerial platform, which is the base for the Council of Ministers in his works. The research problem lies in whether the Iraqi constitutional legislator obliged the Prime Minister to follow transparency when naming his cabinet. And, how far there is legal regulation that enables citizens to be informed of the actions of the Prime Minister when choosing a cabinet in order to ensure the selection of the most qualified personnel to fill ministerial positions. In addition, is there transparency in the numbers and implementation of the government program voted by the House of Representatives when granting confidence to the cabinet? Accordingly, the research should be divided into two requirements. Firstly, the definition of transparency and its legal basis should be recognized through two branches. We devote the first to the definition of transparency, and we show in the second section the legal basis for transparency, and we highlight in the second demand the transparency in the work of the Prime Minister through two branches. We will study in the first the transparency in the field of choosing Ministers, and in the second branch, we will discuss transparency in the ministerial curriculum